Hearing Sex at the Cocktail Party: Biased Sex Ratios Influence Vocal Attractiveness. Issue 1 (3rd April 2018) - Neuhoff, John. G.; Sikich, Taylor N.
ABSTRACT: Visual exposure to unbalanced sex ratios influences perceived facial attractiveness for opposite-sex faces. When opposite-sex faces are scarce they are rated as more attractive than when they are plentiful. The current work examines a vocal-auditory analog of this effect. Participants were assigned to either a high or low opposite-sex vocal exposure condition and reported summary statistics by estimating the percentage of male and female voices in an array of simultaneous talkers. Participants then rated the attractiveness of individual opposite-sex voices. Those in the low opposite-sex exposure condition rated subsequent individual voices of the opposite sex as significantly more attractive than those who were in the high opposite-sex exposure condition. The findings demonstrate that a core visuo-perceptual aspect of mate selection preference also occurs in the auditory domain. The results are consistent with the idea that the attractiveness of opposite-sex partners is an honest signal of fitness and involves multimodal processes that are quickly modulated by the perceived availability of opposite-sex partners in a local environment.